Education, Health And Educational Tasks In The Field Of Physical Education - Gilijova Arzigul Mametmiratovna (Zien Journals, 2022)
In this article,to be able to practically use modern pedagogical technologies and tools, pedagogical tools and skills in the process of improving the teacher's qualifications in the field of education, rehabilitation and educational tasks in the field of physical educationlearningDetermining humanitarian qualities from the works of teachers, analyzing balanced theoretical works from a scientific point of viewsuch issues are disclosed
Keywords: JIslamic culture; jIslamic statephysical education; pedagogicalPerceptual abilities; biomechanics